Primary Education Teachers’ Perceptions of Students’ Learning Disabilities in the Absence of Official Diagnosis A Field Study in Selected Schools of Lattakia Governorate: A Field Study in Selected Schools of Lattakia Governorate (Journal of Hama University, 2026)
The present study aims to explore primary school (first cycle) teachers’ perceptions of the manifestations of learning difficulties among learners in the absence of a formal diagnostic system in Lattakia Governorate. It also seeks to identify differences in these perceptions according to gender (male and female), type of school (regular or inclusive), and academic qualification. In addition, the study aims to determine teachers’ training needs in the field of learning difficulties. The descriptive method was adopted, and a questionnaire was used consisting of two dimensions: teachers’ perceptions of the manifestations of learning difficulties (including three sub-dimensions: cognitive, behavioral, and emotional) and training needs. The sample consisted of 377 male and female teachers in Lattakia schools, selected using simple random sampling.Findings showed that teachers’ perceptions of learning difficulties were at a moderate level (54.1%). Results also revealed significant differences in the cognitive dimension in favor of male teachers, and high training needs in favor of female teachers. No significant differences appeared regarding school type (regular or inclusive). Differences were found in favor of teachers holding a master’s degree across all dimensions. Training needs were highest among teachers with a general university degree or a teacher qualification diploma compared to those with a master’s degree. The greatest need identified was learning strategies to effectively support students with learning difficulties and training in instructional techniques specific to this group.
Keywords: التصور، صعوبات التعلم، مرحلة التعليم الأساسي.